The Baton Rouge interviews : with Alexandre Leupin - Cooper, Kate M. (Glissant, Édouard, 1928-2011. Glissant translation project., 2020)
This collection of interviews is remarkable in the way that it assembles so many of the major strains of Glissant's thought, and stunning in the expansive erudition at work in the composition of that thought. Both in exposition and execution, herein lies the transformative power of Relation.